Hydrological functioning of cattle ranching impoundments in the Dry Chaco rangelands of Argentina - Magliano, Patricio Nicolás (2019)
Rainwater harvesting and associated storage is essential for cattle ranching in the drylands of Argentina and elsewhere. This is the first study to attempt to quantify the hydrological inflows and losses from rainwater harvesting impoundments. To address the direct effect of cattle within impoundments, a typical cattle-affected impoundment was instrumented and compared with that of a similar impoundment but without cattle access. Analysis of the storage dynamics with reference to the controlling variables demonstrated the highly episodic nature of the generation of infiltrationexcess overland flow that recharged the impoundments. The impoundments experienced 43 and 35% of storage loss to open-water-evaporation for the cattle-affected and control impoundments, respectively. Critically, the cattle-effected impoundment lost only 15% of storage to leakage (after cattle consumption was taken into account), while the control lost 65% of its water to basal leakage. Indeed systems modelling of the rainfall-storage dynamics showed that the cattle-affected impoundment, despite consumption by 300 cows, maintained water in the impoundment (per a unit input of rainfall) for longer than the control (a 65- versus 25-day residence time). These results highlight the unintended beneficial effect of cattle trampling on the floor of the impoundment reducing leakage losses.